Facile Synthesis of Carbon Cloth Supported Cobalt Carbonate Hydroxide Hydrate Nanoarrays for Highly Efficient Oxygen Evolution Reaction - Yan, Yubing (Frontiers in Chemistry, 2021)
Developing efficient and low-cost replacements for noble metals as electrocatalysts for the oxygen evolution reaction (OER) remain a great challenge. Herein, we report a needle-like cobalt carbonate hydroxide hydrate (Co(CO3)0.5OH·0.11H2O) nanoarrays, which in situ grown on the surface of carbon cloth through a facile one-step hydrothermal method. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) characterizations demonstrate that the Co(CO3)0.5OH nanoarrays with high porosity is composed of numerous one-dimensional (1D) nanoneedles. Owing to unique needle-like array structure and abundant exposed active sites, the Co(CO3)0.5OH@CC only requires 317 mV of overpotential to reach a current density of 10 mA cm−2, which is much lower than those of Co(OH)2@CC (378 mV), CoCO3@CC (465 mV) and RuO2@CC (380 mV). For the stability, there is no significant attenuation of current density after continuous operation 27 h. This work paves a facile way to the design and construction of electrocatalysts for the OER.